Media Kartu Derivatif dalam Pembelajaran Turunan - I Wayan Laba (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2020)
This study describes an alternative strategy in mathematics teaching and learning on derivative topic using derivative card-based media, which refers to constructivism view. Mathematics teaching and learning using constructivism principles will enable the students to construct their own knowledge/understanding so that their conceptual knowledge becomes more resistant. Meanwhile, derivative card media is an alternative media to help students understand the concepts of differential/derivative through games so that it emerges a meaningful learning.